Challenges for assessment of cohabiting stocks of argentine shortfin squid Illex argentinus using parasites as biological tags - María Paz Gutiérrez; Delfina Canel; Paola E. Braicovich; Ana L. Lanfranchi; Manuel M. Irigoitia; Marcela L. Ivanovic; Nicolás I. Prandoni; Beatriz Elena; Juan T. Timi (International Journal for Parasitology: Parasites and Wildlife)
The Argentine shortfin squid Illex argentinus is one of the most important commercial species for the Argentine fisheries. The understanding of its stock structure is therefore necessary to ensure fishery sustainability and, given the relevance of squids in the regional food web, for biodiversity conservation. An overlap between parasitology and fisheries lies in the use of parasites as biological tags to identify the stock composition of exploited resources, however, the efficiency of this methodology has been questioned for stock assessment in cephalopods. In this work, the value of parasite assemblages of I. argentinus to discriminate between the co-occurring summer spawning stock (SSS) and south patagonic stock (SPS) in a mixing area over the Patagonian continental shelf during summer was evaluated for two cohorts. Five shortfin squid samples corresponding to SSS and SPS were examined for metazoan parasites. The squid size affected the parasite assemblage similarities, conversely, no gender effect on the infracommunities was observed. Multivariate analysis evidenced similarity in parasite assemblage composition and structure between both stocks captured in the mixing area on the same date. This similarity was related to the presence of short-lived trophically transmitted parasites, which are associated with their recently consumed food items and, indirectly, to the oceanographic conditions. The same set of host and environmental variables were identified as the most probable causes of the temporal variability observed in parasite assemblages between SPS cohorts and even intra-cohort. Despite the value of parasites as tags for discriminating squid stocks may have little value when cohabiting stocks are analysed, their variability could serve as a valuable indicator of environmental conditions. The use of parasites as biological tags to discriminate stocks needs to be verified at different spatiotemporal scales, including samples from other non-sympatric stocks in the analyses.